STRATEGIES FOR HANDLING BULLYING IN EDUCATION - Criezta Korlefura; Yulian Hermanus Wenno; Cynthia Petra Haumahu (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Bullying is a serious problem that continues to plague educational environments at various levels. This phenomenon negatively affects students' physical, emotional and academic well-being. This study aims to examine various effective strategies in dealing with bullying in schools. The research method used was literature review. The main strategies include the development of a comprehensive anti-bullying policy, staff and student training, implementation of evidence-based prevention programmes, and creation of a positive school culture. The results showed that a combination of these strategies can significantly reduce the incidence of bullying and increase students' sense of safety at school. The study concludes that addressing bullying requires long-term commitment and co-operation from all relevant parties to create a safe and supportive learning environment for all students.